‘They Say There’s More Equality…’: Women’s Perspectives on Progress and Setbacks in Gender Equality in Northern Iceland During Times of Crisis - Marya Rozanova-Smith; Embla Eir Oddsdóttir; Andrey N. Petrov (Societies, 2025)
Enabling gender equality through the empowerment of women to fully participate in modern society is one of the most critical steps toward sustainable development. However, recent UN reports indicate that the impacts of the COVID-19 pandemic have jeopardized the achievement of Sustainable Development Goal 5 by 2030 in many countries worldwide, including Iceland, which has consistently been ranked as a global leader in gender equality. The main objective of this qualitative study is to examine the gendered impacts of the COVID-19 pandemic by exploring women’s lived experiences during the crisis and its aftermath across the primary domains of gender equality—personal and social. The study is based on 72 in-depth, semi-structured interviews conducted in the Northeastern Region of Iceland (Norðurland eystra) in 2022–2023, utilizing both strength-based and deficit analyses. The findings from the study indicate that, despite high government gender equality standards and support programs, as well as the considerable resilience demonstrated by women during the pandemic crisis, women in Iceland continue to encounter significant constraints to empowerment in achieving genuine gender equality within the personal and social domains. The study outcomes suggest that the further integration of a gender-responsive approach into policy development is crucial for the implementation of more comprehensive, nuanced, and locally adaptive gender equality measures. Advancing such policies will not only strengthen Iceland’s position as a global leader in gender equality but also contribute to its long-term social sustainability.